Pengaruh E-Modul Berbasis Discovery Learning (DL) Terhadap Literasi Sains Siswa Pada Materi Gelombang Bunyi - Sri Wulandari; Hadma Yuliani; Nadia Azizah (Lembaga Bale Literasi, 2023)
Learning media is important to support activities in the learning process. One of them is the use of E-media in the form of online modules, namely the use of DL-based E-modules. The use of DL-based E-modules is used to see the effect on students' scientific literacy material on sound waves MA Hidayatul Insan Palangka Raya class XI. The research uses a quantitative descriptive research type using the Pre-Experimental Designs One – Group Pretest-Posttest Design method. Data analysis from the average pretest score was 34,31 and the posttest average score was 83.282. The results of the data analysis of paired sample t-test obtained tcount > ttable = 2,00191 > 1.753 and one-way significance test = 0.03 <0.05 obtained H1 was accepted so that it was concluded that there was an effect of using DL-based E-module on students' scientific literacy .